2013
DOI: 10.2147/ott.s41343
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-141 is downregulated in human renal cell carcinoma and regulates cell survival by targeting CDC25B

Abstract: Background/objectiveMicroRNAs (miRNAs) are small noncoding RNAs (ribonucleic acids), approximately 22 nucleotides in length, that function as regulators of gene expression. Dysregulation of miRNAs has been associated with the initiation and progression of oncogenesis in humans. The cell division cycle (CDC)25 phosphatases are important regulators of the cell cycle. Their abnormal expression detected in a number of tumors implies that their dysregulation is involved in malignant transformation.MethodsUsing miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…High-throughput technologies have been employed to identify differences in miRNA expression levels between tumor and normal tissues. Recently, increasing number of miRNA profiling datasets have grown rapidly, however, recent miRNA expression profiling datasets showed inconsistent results between the studies due to different technological platforms and small sample size application 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 . Considering inconsistent annotation and ongoing discovery of new miRNAs, different detection methods used by different technological platforms, various methods for data processing and analysis, we are trying to find a meaningful way in which to combine the results of several individual studies in order to increase the statistical power.…”
mentioning
confidence: 99%
“…High-throughput technologies have been employed to identify differences in miRNA expression levels between tumor and normal tissues. Recently, increasing number of miRNA profiling datasets have grown rapidly, however, recent miRNA expression profiling datasets showed inconsistent results between the studies due to different technological platforms and small sample size application 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 . Considering inconsistent annotation and ongoing discovery of new miRNAs, different detection methods used by different technological platforms, various methods for data processing and analysis, we are trying to find a meaningful way in which to combine the results of several individual studies in order to increase the statistical power.…”
mentioning
confidence: 99%
“…MiR-141 is widely expressed in many human malignant tumors and is highly expressed in tumors such as ovarian cancer (Mateescu et al, 2011), NSCLC tissues (Mei et al, 2014), nasopharyngeal cancer (Zhang et al, 2010), prostate cancer (Seol et al, 1996), thyroid papillary cancer (van Bokhoven et al, 2003), and colorectal cancer (Hu et al, 2010), but has low level in nasopharyngeal carcinoma (Li M. et al, 2019), hepatocellular carcinoma (Hou et al, 2019), esophageal cancer (Imanaka et al, 2011), non-small cell lung cancer , breast cancer (Finlay-Schultz et al, 2015), and renal cell carcinoma (Yu et al, 2013). These results indicate that miR-141 plays a dual role of an oncogene or tumor suppressor by regulating target genes, which provides a new alternative for treatment in the course of different tumorigeneses and developments.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers observed that miRNAs post-transcriptionally regulated the expression of more than 30% of protein coding genes by translational repression, which also regulated the expression of several putative target genes by binding to a complementary sequence predominantly in their untranslated region. However, the bindings are not always completely complementary, particularly in mammals ( 29 , 30 ). Moreover, further research should be conducted to determine the roles and target genes of miR-184 in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%